OPTIMASI AMOBILISASI UREASE DARI Schizzosaccharomyces pombe MENGGUNAKAN MATRIK Ca-ALGINAT - Maharani, Laras Dwi; Prasetyawan, Sasangka; Mahdi, Chanif (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Urease immobilization is required to be used in repetition The enzyme hydrolize urea to be ammonia and carbondioxide. Urease was isolated from Schizzosaccharomyces pombe and was purified through precipitation by using ammonium sulphate at 30-45% saturation level, followed by dialysis. Urease was immobilized by entrapment method in a matrix of Ca-alginate. The study aimed to determine optimum concentration of Na-alginate and enzym concentration. In this research, Na-alginate concentration (1,5 ; 2 ; 2,5 ; 3 ; 3,5) % (w/v) and variation of urease concentration (0,840; 1,680; 2,520; 3,360; 4,200) mg/mL. Protein content was determined by Biuret reagen and enzyme activity was determined as the amount of mikromol amonia per minute, and resulted amonia was analyzed by Nessler method. The results showed that the optimum condition of immobilization urease is achieved on 3% Na-alginate solution and 2,52 mg/ml urease yielding in 2,52 mg of entrapped enzyme/gram Ca-alginate and the activity of 0,55 Units. Key words: activity, Ca-alginate, Schizzosaccharomyces pombe, urease.